Effects of national housing quality standards on hospital emergency admissions: a quasi-experiment using data-linkage. (November 2016) - Rodgers, S E; Bailey, R; Johnson, R; Berridge, D; Poortinga, W; Dunstan, F; Lyons, R A
Abstract: Background: National housing quality standards are now being applied throughout the UK. The Welsh Government has introduced the Welsh Housing Quality Standards. A housing improvement programme in Wales has been delivered through one local authority to bring 9500 homes up to standard. Homes received multiple elements, including new kitchens, bathrooms, windows and doors, boilers, insulation, and wiring, through an 8 year rolling work programme. The study aimed to determine the impacts of the different housing improvements on hospital emergency admissions for residents over 60 years of age. Methods: Intervention homes (council homes that received at least one element of work) were data linked to individual health records of residents. Counts of admissions for respiratory and cardiovascular conditions, and for falls and burns, were obtained retrospectively for each individual in a dynamic housing cohort (Jan 1, 2005, to March 31, 2015). The criterion for the intervention cohort was for someone to have lived in any one of the 9500 intervention homes for at least 3 months within the intervention period. Counts were captured for up to 123 consecutive months for 7054 individuals in the intervention cohort and analysed in a multilevel approach to account for repeated observations for individuals, nested within geographical areas. Negative binomial regression models were constructed to determine the effect on emergency admissions for those living in homes compliant for each element of work compared with those living in homes that were non-compliant at that time. We adjusted for background trends in the regional general population, and for other confounding factors. Findings: For residents 60 years old and over there was a reduction in admissions for people with compliant boilers (rate ratio 0·71, 95% CI 0·67–0·76), loft insulation (0·87, 0·80–0·95), wall insulation (0·74, 0·69–0·80), and windows and doors (0·56, 0·52–0·61) compared with those living in homes that were non-compliant for those work elements. Interpretation: Improving housing to national standards reduces the number of emergency admissions to hospital for older residents. Strengths of the data-linkage approach included the retrospective collection of complete baseline and follow-up data using routine data for a long-term intervention, and large scale regional adjustment. Funding: National Institute for Health Research (NIHR) Public Health Research programme (project number 09/3006/02).